The effects of defoliation and rootpruning on cocksfoot and perennial ryegrass and the influence of soil moisture on root initiation : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Field Husbandry, University of New Zealand - Edmond, D. B. (Massey University, 1949)
The world is short of food (1). The population of the world is unequally distributed in relation to the productive ability of the land. Countries, where an extension of the farmed area is possible, are handicapped by a lack of available labour. In general these are the countries where production has not, as yet, reached a maximum level. As labour hinders extension an endeavour must be made to utilise present farm areas in the most efficient manner possible, In this way surpluses of food may be accumulated in these countries, e.g. New Zealand, for despatch to needy areas where the consumption of food is at a low level. New Zealand produces animal products in quantity. To increase this quantity better use must be made of our chief stock food - grass. By more efficient use of our grasslands the production of our existing herds and flocks will be increased. while an increase in our animal population will be inevitable. [From Introduction]
Keywords: Forage plants; Roots; Ryegrasses; Orchard grass; Varieties